Cancer Stem Cells: A Potential Breakthrough in HCC-Targeted Therapy - Wu, Yafei; Zhang, Jigang; Zhang, Xue; Zhou, Heming; Liu, Gaolin; Li, Qin (Frontiers in Pharmacology, 2020)
Cancer stem cells (CSCs) are subpopulations of cells with stem cell characteristics that produce both cancerous and non-tumorigenic cells in tumor tissues. The literature reports that hepatocellular carcinoma (HCC) cells are closely related to CSCs and promote their malignant features such as high invasion, drug resistance, easy recurrence, easy metastasis, and poor prognosis. This review discusses the origin, molecular and biological features, functions, and applications of CSCs in HCC in recent years; the goal is to clarify the importance of CSCs in diagnosis and treatment and explore their potential value in HCC-targeted therapy.